2008
DOI: 10.1128/jvi.02198-07
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Immediate-Early Protein Zta Co-Opts Mitochondrial Single-Stranded DNA Binding Protein To Promote Viral and Inhibit Mitochondrial DNA Replication

Abstract: Disruption of cellular metabolic processes and usurpation of host proteins are hallmarks of herpesvirus lytic infection. Epstein-Barr virus (EBV) lytic replication is initiated by the immediate-early protein Zta. Zta is a multifunctional DNA binding protein that stimulates viral gene transcription, nucleates a replication complex at the viral origin of lytic replication, and inhibits cell cycle proliferation. To better understand these functions and identify cellular collaborators of Zta, we purified an epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…To elucidate how Zta activates transcription, MALDI-TOF mass spectrometry was performed and Ku80 was found to interact with His-Zta fusion protein bound to Ni 2+ -charged beads (data not shown). This verifies the results of Wiedmer et al (2008) and Bailey et al (2009), who showed that Ku80 is a binding partner of, and is co-purified with, Zta. Therefore, these results motivated us to investigate the interaction between the two proteins and how the interaction affects the function of Zta.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…To elucidate how Zta activates transcription, MALDI-TOF mass spectrometry was performed and Ku80 was found to interact with His-Zta fusion protein bound to Ni 2+ -charged beads (data not shown). This verifies the results of Wiedmer et al (2008) and Bailey et al (2009), who showed that Ku80 is a binding partner of, and is co-purified with, Zta. Therefore, these results motivated us to investigate the interaction between the two proteins and how the interaction affects the function of Zta.…”
supporting
confidence: 78%
“…Earlier studies performed MALDI-TOF mass spectrometric analysis and demonstrated that Ku80 was co-purified with Zta from ZKO-293 and HEK cells (Bailey et al, 2009;Wiedmer et al, 2008), suggesting that these two proteins interact. Our studies also confirmed that Ku80 co-purified with histidinetagged Zta by using Ni 2+ -charged beads (Qiagen) and MALDI-TOF mass spectrometry (data not shown).…”
Section: Analysing the Interaction Between Zta And Ku80mentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Following infection with Epstein-Barr virus, this protein has been shown to be relocalized to the nucleus, where it stimulates viral replication (84). Surprisingly, however, the protein was not detected by immunofluorescence in the nuclei of either infected or transfected HeLaAAVtCR cells ( Table 2).…”
mentioning
confidence: 79%
“…UL12.5 localizes predominantly to mitochondria, where it triggers massive degradation of mitochondrial DNA early during HSV replication [132]. In addition to that UL12.5 has been found to acts directly within the mitochondrial matrix to degrade mitochondrial DNA by its nuclease activities [133].…”
Section: Use Of Molecular Mimicry By Viruses To Invade Mitochondriamentioning
confidence: 99%